Evolution Temporelle Et Spatiale De La Macroflore Benthique De L’ecosysteme Lagunaire De Nador - Mohamed, Najih; Nadia, Berday; Nor-dine, Rezzoum; Fouad, Mounir; Abdeljaouad, Lamrini; Driss, Nachite (European Scientific Journal, ESJ, 2016)
The objective of the present study undertaken in 2011is to evaluate the status of the benthic macroflora of the Nador lagoon after the management works carried out in 2009 to improve the lagoon environmental quality. Relying on a previous study carried out in 1987, the results of analysis in 2011 showed that the lagoon seabed macroflora recorded a marked decline and an overall change in its distribution and specific composition. The marine Phanerogams, represented by Cymodocea and Zostera, in association with Caulerpa, which were the main vegetationin 1987, were replaced by a macroflora highly dominated by macroalgae (64.3% of the total area), essentially represented by Rhodophyceae (58% of total area).In 2011, the genus Alsidiumwas the main representative in the macroflora(55% of total area),while the genus Caulerpa, and Phanerogamssaw their area of occurrence regress to 25.6% and 18% respectively.